The distribution of contract durations across firms: a unified framework for understanding and comparing dynamic wage and price setting models - Huw Dixon (European Central Bank (ECB), 2006)
This paper shows how any steady state distribution of ages and related hazard rates can be represented as a distribution across firms of completed contract lengths. The distribution is consistent with a Generalised Taylor Economy or a Generalised Calvo model with duration dependent reset probabilities. Equivalent distributions have different degrees of forward lookingness and imply different behaviour in response to monetary shocks. We also interpret data on the proportions of firms changing price in a period, and the resultant range of average contract lengths.
Keywords: E50; 330; Calvo; Contract length; hazard rate; steady state; Taylor; Preisrigidität; Vertragstheorie; Geldpolitik; Schock; Dynamisches Gleichgewicht; Theorie